Kinetic Memory Based on the Enzyme-Limited Competition - Hatakeyama, Tetsuhiro S.; Kaneko, Kunihiko (PLOS Computational Biology, 2014)
Author Summary Cellular memory exists in a wide range of organisms from prokaryotes to eukaryotes and can persist, in some cases, for days at a time. Mounting evidence supports the notion that cells indeed can retain information associated with previous environmental exposures via posttranslational modifications. Molecules with multiple modification sites, such as those regulated by changes in methylation or phosphorylation, are expected to play an important role in this process. However, how such epigenetic cellular memory is preserved is not yet fully understood, and theoretical models must be developed. Here we demonstrate that long-term maintenance of the modification state occurs as a result of enzyme-limited competition in a wide class of multimeric protein systems consisting of modification reactions that share enzymes. This maintenance is explained by very slow relaxation resulting from the limited amount of enzymes available. Therefore, memory is easily affected by continuous changes in external stimuli. The proposed mechanism for kinetic memory does not require any fine-tuning in system parameters and is applied to a broad class of cellular memory including long-term potentiation of synapses.